An Investigation on The Master Printing Plates Development Attending to Micron Sizes Employing a Flexographic Micro Scalar Printing Technique - Shariff, Lisa Yasmine (Research Progress in Mechanical and Manufacturing Engineering, 2022)
Master printing plates play a major part in the flexographic micro scalar printing technique. In the industry, there is no substantial use on master printing plates developed for micron sizes using a flexographic micro scalar printing technology. Therefore, an investigation on the potential types of master plate produced used in the process of flexographic micro scalar printing technique was conducted. A step-by-step approach by designing the master mould, printing of the master mould plates and printing of multiple fine lines needs to be carried out in advance to help comprehend this process that is influenced by many interacting parameters. The characteristics of the printing plates are among the number of parameters which plays a big role in this study. Printing trials of the master mould plates using different printers were carried out to compare the compatibility and the accuracy of the developed fine solid lines on the mould plates.